Risk Attitude Of Insured And Non-Insured Dairy Farmers: A Comparative Analysis - Khan, Mohd. Ameer; Chander, Mahesh; Bardhan, D. (Indian Journal of Veterinary Sciences and Biotechnology, 2016)
The present study was conducted to know the farmers attitude towards different sources of risk. Two hundred and forty cattle and buffalo owners were selected randomly from Gorakhpur district of Uttar Pradesh consisting 120 dairy farmers who had insured at least one cattle or buffalo from their herd and another 120 dairy farmers who had never insured their dairy animals. Findings showed that there were important differences in farmers’ risk attitudes. Attitude to risk affects farmers’ decision in input utilization and technology adoption. Programs and policies for farmers would deliver better results if these incorporate farmers’ risk attitude, risk sources and its relationships with socio-economic and geographical locations.
Keywords: Risk attitude; Dairy farmers; Insurance; Cattle and buffalo